The Influence Of Communication, Work Systems, And Motivation On Employee Performance At PT. Bali Kado Johor - Clarissa Clarissa; Deni Faisal Mirza (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the influence of communication, work systems, and motivation on employee performance at PT. Bali Kado Johor. The company, established in 2018, operates as a retail business with several outlets in Medan City. The research employs a quantitative approach with data analysis conducted using SmartPLS. The findings indicate that communication has a positive and significant influence on employee performance, with a T-statistic value of 2.397 and a P-value of 0.017. Similarly, work systems also show a positive and significant impact, with a T-statistic value of 3.559 and a P-value of 0.000. However, motivation does not have a significant effect on employee performance, as shown by a T-statistic value of 1.573 and a P-value of 0.125. Overall, the variables of communication, work systems, and motivation contribute to employee performance, with significant effects observed in communication and work systems.